Implementation of Question Bank Applications for Website-Based Students - Pandi Barita Nauli Simangunsong; Satria Yudha Prayogi; Sony Bahagia Sinaga (INFOKUM, 2022)
Every tertiary institution, both private and public, has students with high and low scores. This also happened at the Catholic University of Santo Thomas, a private university in Medan, North Sumatra. So a solution is needed that can help students improve their grades, and one way is to make the previous year's questions a reference for student learning. So, a service or application is also needed that accommodates all the questions that exist at a university such as a question bank that can be accessed easily. The Waterfall method is used for the process of developing system engineering and software in an orderly and systematic manner. This method is taken with a systematic approach starting from needs analysis, system and software design, implementation, unit testing and development. In this application, users can upload questions they have, look for questions as references, mark questions that are considered important and download questions that are needed. Where is the purpose of making this application, students no longer have to bother looking for material references through the questions that were tested before. Where is the purpose of making this application, students no longer have to bother looking for material references through the questions that were tested before. The Waterfall method is used for the process of developing system engineering and software in an orderly and systematic manner. This method is taken with a systematic approach starting from needs analysis, system and software design, implementation, unit testing and development. In this application, users can upload questions they have, look for questions as references, mark questions that are considered important and download questions that are needed. Where is the purpose of making this application, students no longer have to bother looking for material references through the questions that were tested before. In this application, users can upload questions they have, look for questions as references, mark questions that are considered important and download questions that are needed. Where is the purpose of making this application, students no longer have to bother looking for material references through the questions that were tested before. In this application, users can upload questions they have, look for questions as references, mark questions that are considered important and download questions that are needed. Where is the purpose of making this application, students no longer have to bother looking for material references through the questions that were tested before.